Removable functional group strategy for regiodivergent Wittig rearrangement products - Alam, Md Nirshad; Lakshmi, K. M.; Maity, Pradip (Organic & Biomolecular Chemistry, 2018)
1,2] and [2,3] Wittig rearrangements are competing reaction pathways, often leading to uncontrollable product distribution. We employ a single removable functional group to fulfill the dual role of attaining a reversible [2,3] and stabilizing radical intermediate for the [1,2] path to obtain both the Wittig products selectively for a broad range of substrates.